Integrasi Transmisi Otomatis Untuk Kendaraan Listrik yang Dikonversi: Pendekatan GT-Suite - Setiawan, Yosua; Said, Mohd Farid bin Muhamad (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2025)
The growing adoption of electric vehicles (EVs) in Southeast Asia, particularly in Indonesia and Malaysia, is driven by policy incentives such as road tax exemptions and relaxed traffic restrictions. This study investigates the feasibility and performance impact of integrating a stock automatic transmission into a converted internal combustion engine (ICE) vehicle, replacing the commonly used single gear or manual transmissions in typical EV conversions. Using GT-Suite simulation software, a detailed model of a converted Toyota Avanza was developed to evaluate key performance metrics including acceleration, top speed, driving range, and energy consumption. Simulation results indicate that integrating an automatic transmission improves acceleration performance, reducing the 0–100 km/h time by 0.7 seconds compared to a single-gear configuration. Although the top speed is mechanically limited by the transmission's maximum input speed, the vehicle achieved a marginally higher top speed (191.3 km/h) and reached it 1.8 seconds faster. During range simulations under the New European Driving Cycle (NEDC) and constant highway driving at 100 km/h, the automatic transmission variant demonstrated a longer driving range—up to 7% farther—while also improving energy consumption from 8.55 km/kWh to 8.77 km/kWh.